CULTIVATION OF SELF-MANAGEMENT AS A FILTER OF KOREAN WAFE INFLUENCE AMONG STUDENTS - M, Rahma (Universitas Negeri Makassar, 2023)
This article discusses the cultivation of self-management for Dance students as a filter to counteract outside lifestyle influences including the influence of Korean Wafe, with an innovative concept of self-awareness (mindfulness), while still having full awareness of thoughts, feelings, and focusing on goals. The research method used in this article is a theoretical study. Self-awareness is needed in carrying out social interactions, especially for students because this also affects the learning process which can fail if you are not able to manage or control yourself properly, especially from the influence of the social environment. Mindfulness as a form of inculcating self-management in students is a theory that can be instilled because it can help students change their perspective on something so that they can filter out the influences that can arise from the surrounding environment. Something that becomes a trend in society doesn't need to be avoided but it should be used to enrich our insights, especially for dance students, they should be able to take advantage of the good things caused by the boom in the Korean style, especially in dance creation.